2007
DOI: 10.1021/bi0616347
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Spectroscopic Characterization of Type II Isopentenyl Diphosphate Isomerase from Thermus thermophilus:  Evidence for Formation of Substrate-Induced Flavin Species

Abstract: Type II isopentenyl diphosphate (IPP) isomerase catalyzes the interconversion of IPP and dimethylallyl diphosphate (DMAPP). Although the reactions catalyzed by the type II enzyme and the well-studied type I IPP isomerase are identical, the type II protein requires reduced flavin for activity. The chemical mechanism, including the role of flavin, has not been established for type II IPP isomerase. Recombinant type II IPP isomerase from Thermus thermophilus HB27 was purified by Ni 2+ affinity chromatography. Aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
121
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(135 citation statements)
references
References 51 publications
13
121
1
Order By: Relevance
“…The λ max value at 435 nm is unusual for flavoproteins but is most consistent with a neutral reduced FMN (as suggested previously for IDI-2 (22, 31)), which has been observed to have a λ max value anywhere from 390 to 450 nm, depending on the hydrophobicity and rigidity of the active site environment (32)(33)(34)(35). Consistent with previous photoreduction studies (22), a neutral semiquinone (E•FMN sem ) could be generated under anaerobic conditions if 2 mM IPP was pre-incubated with E•FMN ox prior to a 2 min photoreduction. On the basis of the ε 583 (3300 M −1 cm −1 ) value determined previously for the S. aureus IDI-2-bound FMN sem (21), the concentration of FMN sem in this photoreduced sample is estimated to be 25 µM (or about 31% of the total E•FMN concentration).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The λ max value at 435 nm is unusual for flavoproteins but is most consistent with a neutral reduced FMN (as suggested previously for IDI-2 (22, 31)), which has been observed to have a λ max value anywhere from 390 to 450 nm, depending on the hydrophobicity and rigidity of the active site environment (32)(33)(34)(35). Consistent with previous photoreduction studies (22), a neutral semiquinone (E•FMN sem ) could be generated under anaerobic conditions if 2 mM IPP was pre-incubated with E•FMN ox prior to a 2 min photoreduction. On the basis of the ε 583 (3300 M −1 cm −1 ) value determined previously for the S. aureus IDI-2-bound FMN sem (21), the concentration of FMN sem in this photoreduced sample is estimated to be 25 µM (or about 31% of the total E•FMN concentration).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, they suggested that the enzyme-bound FMN intermediate that forms during the normal reaction is consistent with a neutral reduced dihydroflavin (4, Scheme 2). Although the steady-state kinetic parameters have been reported for a few IDI-2 enzymes (13,15,18,21,22,25), the nature of the rate limiting step(s) in the catalytic mechanism is unknown. In this paper, we report the investigation of the FMN intermediate formed during the catalysis of S. aureus IDI-2 using UV-vis and EPR spectroscopies.…”
mentioning
confidence: 99%
See 3 more Smart Citations